2013
DOI: 10.1002/lary.24462
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL‐33 and its receptor ST2 in chronic rhinosinusitis with nasal polyps

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 29 publications
4
44
3
Order By: Relevance
“…540,541 Some evidence suggests that IL-33 may play a role as well, but these studies have yet to demonstrate increased expression of this cytokine at the protein level in NP tissue. 374,[542][543][544] In regard to IL-25, evidence in CRS is scant. As mentioned earlier in this section EC chemokines also play a major role in the attraction and activation of innate effector cells including eosinophils, mast cells, neutrophils, macrophages, and likely ILCs.…”
Section: Discussionmentioning
confidence: 99%
“…540,541 Some evidence suggests that IL-33 may play a role as well, but these studies have yet to demonstrate increased expression of this cytokine at the protein level in NP tissue. 374,[542][543][544] In regard to IL-25, evidence in CRS is scant. As mentioned earlier in this section EC chemokines also play a major role in the attraction and activation of innate effector cells including eosinophils, mast cells, neutrophils, macrophages, and likely ILCs.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, expression of IL-33 and its receptor ST2 was also investigated in patients with CRS,1921 and two of these studies reported elevated expression of ST2,19 20 implying that the IL-33/ST2 pathway may function in nasal polypogenesis. Despite these findings, the specific role of IL-33 in the pathophysiology of patients with CRSwNP still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…An eosinophil count of 50 per microscopic field (magnification ×400) was chosen to distinguish between ECRSwNP and nECRSwNP, as described previously [9]. Symptom scores were assessed according to the visual analog scale (VAS) and Sino-Nasal Outcome Test-20 (SNOT-20).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found that NPs of Asian patients are less eosinophilic as compared to those of a Western population and that mast cells might be involved as much as eosinophils in the mucosal pathogenesis of NPs in Asian patients [9]. Other studies have found that interleukin-33 (IL-33) is involved in the pathogenesis of various allergic diseases and, therefore, may act as a therapeutic target.…”
Section: Introductionmentioning
confidence: 99%